Herida penetrante de córnea por trauma contuso en paciente masculino de 32 años - Chaucanes Erazo, Roció Del Carmen (2021)
At present, ocular trauma is one of the most frequent events and for this reason they attend ophthalmological consultation, the causes are presented in environments such as: traffic accidents, work, activities at home, sports and recreational areas, the most affected people they are children and young adults. In the world, the figures suggest that it is a source of blindness, monocular or binocular. To publicize the causes, symptoms, classification, treatment and prognosis, a synopsis will be made for clinical verification, under an initial assessment. It is considered that this type of injury, can present a risk situation before the vision and is considered an ophthalmological emergency, other disciplines are involved, to prevail the integrity of the patient and his organs.